Quantifying the cost of passive smoking on child health: evidence from children's cotinine samples - Paul Frijters; Michael A. Shields; Stephen Wheatley Price; Jenny Williams (Institute for the Study of Labor (IZA), 2006)
Passive smoking is a major public health issue. This paper documents the main risk factors that determine children's exposure to passive smoke, and then uses econometric techniques to provide a new economic quantification of the impact of this exposure on child health. Such information is valuable to policy-makers when deciding upon the amount of resources to direct towards the problem of passive smoking. One of our main contributions is the use of a large nationally representative sample of children drawn from the Health Survey for England, for whom we match parental and household smoking and demographic characteristics. We also utilise an objective measure of children's exposure, namely, the level of cotinine - a metabolite of nicotine - in their saliva. We find that both parental and child carer smoking behaviour, as well as area deprivation, are major risk factors in determining children's exposure to passive smoke. Accounting for the potential measurement error in cotinine in our estimations, we have calculated that for a child who is exposed to a high number of passive smoking risk factors, the shadow price or income-equivalence of such exposure is 16,000 (US30,000) per year. A further policy-related result is that comprehensively controlling for child passive smoking does not explain the observed gradient between household income and child health.
Keywords: D1; I1; 330; passive smoking; child health; parental smoking; cotinine; income